2016
DOI: 10.1002/lno.10460
|View full text |Cite
|
Sign up to set email alerts
|

The Synechococcus cell surface protein SwmA increases vulnerability to predation by flagellates and ciliates

Abstract: The genus Synechococcus, a major contributor to ocean productivity, exhibits wide genetic variability and a distinct biogeography of genetic subgroups. Synechococcus sp. strain WH8102 is a motile Sargasso Sea isolate belonging to Clade III in subcluster 5.1. Non‐flagellar motility in WH8102 depends upon two large cell surface proteins, SwmA and SwmB. In the marine plankton, Synechococcus can experience high rates of mortality from protist predators, suggesting strong selective pressure for the maintenance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…We also found similar heterogeneity between isolates collected in 2011 and 2013 despite differences in culturing time. Further supporting an increased occurrence of genomic heterogeneity among LL/LG colonies, we found increased frequencies of genes in LL/LG genomes that may facilitate nonclonal colony formation: (a) NeuB that synthesizes sialic acids, which are a component of cyanobacterial extracellular polymeric substances (Strom, Bright, Fredrickson, & Brahamsha, 2017;Zippel & Neu, 2011) and play important roles in cellular recognition and adhesion (Gunawan et al, 2005); (b) sialidases that may facilitate cellular adhesion by uncovering carbohydrate receptors that are recognized by bacterial adhesins (Vimr, 1994);…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We also found similar heterogeneity between isolates collected in 2011 and 2013 despite differences in culturing time. Further supporting an increased occurrence of genomic heterogeneity among LL/LG colonies, we found increased frequencies of genes in LL/LG genomes that may facilitate nonclonal colony formation: (a) NeuB that synthesizes sialic acids, which are a component of cyanobacterial extracellular polymeric substances (Strom, Bright, Fredrickson, & Brahamsha, 2017;Zippel & Neu, 2011) and play important roles in cellular recognition and adhesion (Gunawan et al, 2005); (b) sialidases that may facilitate cellular adhesion by uncovering carbohydrate receptors that are recognized by bacterial adhesins (Vimr, 1994);…”
Section: Discussionsupporting
confidence: 60%
“…We also found similar heterogeneity between isolates collected in 2011 and 2013 despite differences in culturing time. Further supporting an increased occurrence of genomic heterogeneity among LL/LG colonies, we found increased frequencies of genes in LL/LG genomes that may facilitate nonclonal colony formation: (a) NeuB that synthesizes sialic acids, which are a component of cyanobacterial extracellular polymeric substances (Strom, Bright, Fredrickson, & Brahamsha, ; Zippel & Neu, ) and play important roles in cellular recognition and adhesion (Gunawan et al, ); (b) sialidases that may facilitate cellular adhesion by uncovering carbohydrate receptors that are recognized by bacterial adhesins (Vimr, ); (c) pfam06229 (FRG1‐like domain) that contains a Hydra spp. gene linked to this freshwater cnidarian's ability to adhere to underwater surfaces (Rodrigues et al, ); and (d) a bacterial adhesin (pfam03865: haemolysin secretion/activation protein ShlB/FhaC/HecB) (Moslavac et al, ) that facilitates adhesion to other cells in pathogenic and symbiotic interactions (Hooper & Gordon, ).…”
Section: Discussionsupporting
confidence: 58%
“…Additionally, Prochlorococcus may be important as a food source because they are present at high levels in the SCM. The cell membranes of Prochlorococcus are covered with proteins 59 and release monosaccharides 60 , the extracellular exudates are composed of low-molecular-weight compounds 61 , and the extracellular vesicles contain rich nutrients such as lipids, proteins, and nucleic acids 62 , 63 . In seawater, it is known that transparent exopolymer particles (TEPs) exist and are mixed with a substantial amount of protein-rich amorphous particles 64 66 .…”
Section: Discussionmentioning
confidence: 99%
“…; Strom et al. ), food nutritional quality (John and Davidson ; Shannon et al. ; Siuda and Dam ), and physiology of the prey (Verhagen et al.…”
mentioning
confidence: 99%
“…Grazing selectivity is influenced by various factors including the growth environment and the morphological and physiological features of the prey (Ng et al 2017). In fact, many factors, for example prey size (Hansen 1992;Jakobsen and Hansen 1997;Jakobsen and Tang 2002), prey motility (Boenigk et al 2001;Buskey 1997), biochemical composition of prey (Ng et al 2017), surface structure variation in prey (Monger et al 1999;Strom et al 2017), food nutritional quality (John and Davidson 2001;Shannon et al 2007;Siuda and Dam 2010), and physiology of the prey (Verhagen et al 1993), have been reported to influence the feeding behaviour of protozoa on algal prey. Knowledge of the interaction between protozoa and phytoplankton is very helpful in interpreting how the underlying mechanisms drive feeding selectivity in planktonic protists (Roberts et al 2011;Strom 2002); however, compared with other groups, considerably less attention has been paid to mixotrophic flagellates by experimental ecologists (Esteban et al 2010;Tillmann 2004).…”
mentioning
confidence: 99%